Efektifitas pemakaian ulang ginjal buatan - Armelia, Linda (Jurnal Kedokteran YARSI, 2008)
Hemodialysis is a therapy for patient with end state renal diseases, but it is very expensive specially dialyzer. Now we could use a reuse of dialyzer to reduce the cost. The aim of this study was to examine the effectiveness of dialyzer reuse and its frequent possible reuse. A prospective study with the comparative experimental approach was carried out. The population was all patient with end state renal diseases underwent twice hemodialysis in a week at fifth hours in each period at least within three months using acetate dialysate and reuse dialyzer in the Dialysis Unit. Sample size was 20 subjects determined based on time continuum It was concluded that the reuse dialyzer could be used 6,06+2,01 times without negative influence on dialysis adecuacy.